2015
DOI: 10.1002/cncy.21615
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection and p16 promoter methylation as predictors of ASC‐US/LSIL progression

Abstract: were subjected to correlation analysis between cytology and histology. Disease regression was defined as a reversion to normal or benign cellular changes, disease persistence as maintenance at ASC-US/LSIL, and disease progression as progression to HSIL. Data regarding clinical parameters were obtained from medical records. Methylation-specific polymerase chain reaction was performed using cytology samples to evaluate methylation of the p16 promoter. RESULTS: Of 165 cases, 131 (79.4%) regressed, 23 (13.9%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Comparing the prevalent histopathological result in ASC cytologies, ASC-US was significantly associated with LSIL or better outcome, whereas ASC-H was more associated with HSIL or worst outcome, in agreement to other authors [4, 11, 40, 41]. In the present study, 13.33% of ASC-US and 64.71% of ASC-H biopsies resulted in HSIL or higher, quite significant numbers indicating a need for follow-up.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparing the prevalent histopathological result in ASC cytologies, ASC-US was significantly associated with LSIL or better outcome, whereas ASC-H was more associated with HSIL or worst outcome, in agreement to other authors [4, 11, 40, 41]. In the present study, 13.33% of ASC-US and 64.71% of ASC-H biopsies resulted in HSIL or higher, quite significant numbers indicating a need for follow-up.…”
Section: Discussionsupporting
confidence: 81%
“…These results rarely cause concerns that more significant lesions may be present since 1/3 to 2/3 are HPV negative [10, 11]. There is important regional variation not only in the proportion of cytological atypias that are positive for HPV but also in the worldwide distribution of high-risk HPV [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis, on the basis of data from over 3000 subjects, we found that the hypermethylation rates in LSIL, HSIL and CC specimens were gradually increased, resulting in a growing trend in effects of P16 INK4a hypermethylation on susceptibility to LSIL, HSIL and CC. These results, combined with the previous epidemiological evidence that P16 INK4a hypermethylation was correlated with the progression of LSIL to HSIL [39, 42], suggest that P16 INK4a promoter hypermethylation may be an epigenetic marker for the progression of cervical carcinogenesis. Hence, detecting P16 INK4a hypermethylation may help clinicians to determine whether patients with cervical neoplasia are in disease regression, persistence or progression.…”
Section: Discussionsupporting
confidence: 70%
“…As large-scale clinical studies have confirmed that the HPV-based screening method possesses a high sensitivity and is easy to repeat, this method is currently recognized as the gold standard for clinical HPV testing. However, it has low specificity [19,20]. Therefore, how to improve the specificity of HPV detection in screening for cervical cancer and avoid over-treatment of patients with positive HPV infection have become major topics of interest.…”
Section: Discussionmentioning
confidence: 99%